Giant Condyloma Acuminatum in a Woman with AIDS - Laila Nuranna (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To describe a case of Giant Condyloma Acuminatum with aspect of HIV and some concerns about the CD4. Result: We describe 2 cases, the first case is a giant Condyloma in HIV patient and the second case is a giant Condyloma in pregnant woman. The patient in the first case was a 40-year-old woman with AIDS (CD4 is 290) who was undergoing anti-retroviral therapy. She was found to have a giant condyloma acuminatum of the vulva. Electrocautery excision was performed, and afterwards the quality of life has improved significantly. The second case patient is a 30-year-old G4P3A0 woman with a giant condyloma acuminatum. She was 30 weeks pregnant with a single fetus. On the external genitalia there was a giant condyloma mass on the vulva extending towards the peri-anal area, obstructing the introitus. The electrocautery excision was performed. She was discharged from the hospital on the second day in good condition. She had a spontaneous delivery after reaching full term. Conclusion: Although the giant Condyloma Acuminatum is combined with HIV, but it’s not as difficult as imagined because the tumor’s base is not wide, but shaped like inverted mushroom and it is not necessary to do local flap reconstruction. [Indones J Obstet Gynecol 2012; 36-4: 206-10] Keywords: electrocautery excision, giant condyloma acuminatum, surgery in AIDS